Childfree in Muslim Families: A Comparative Study of Maqaṣid al-Syari’ah and Modern Reproductive Rights - Ahmad Khotim (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2026)
The discourse of childfree, a conscious decision by married couples to remain childless throughout their marriage, has shifted from a mere private choice to a global ideological movement challenging traditional family structures, including within the Muslim family landscape. This study aims to comparatively dissect the dialectic between the concept of childfree in Muslim families through two conflicting paradigms: Maqaṣid al-Syarī’ah (specifically the pillar of ḥifẓ al-nasl ) and the doctrine of Modern Reproductive Rights (bodily autonomy). The research method used is a juridical-normative approach with a comparative approach and a philosophical approach. The results of the study indicate a deep epistemological gap. Modern Reproductive Rights places individuals as the absolute owners of their bodies (anthropocentric), thus giving rise to absolute freedom to refuse procreation. In contrast, Maqaṣid al-Syarī’ah views reproduction within a theocentric framework, where the body and offspring are divine trusts oriented towards the public good (maṣlaḥah ‘ammah) and the preservation of civilization. This study concludes that the concept of voluntary childfree without medical excuse is rejected by the consensus of Maqaṣid al-Syarī’ah because it reduces the main essence of marriage, but in the corridor of positive law, it is in the area of ​​​​the unavailability of formal sanctions (rechtsvacuum), so its enforcement rests on strengthening the legal culture of Muslim society.